1986
DOI: 10.1111/j.1476-5381.1986.tb09484.x
|View full text |Cite
|
Sign up to set email alerts
|

Postjunctional inhibition of contractor responses in the mouse vas deferens by rat and human calcitonin gene‐related peptides (CGRP)

Abstract: 3 The inhibitory effect of human ax-CGRP was not antagonized by either propranolol (300 nM) or idazoxan (300 nM), although in the same tissues these latter two drugs reduced responses to isoprenaline and clonidine respectively.4 Rat a-CGRP (100 nM) and human x-CGRP(1.0 yM) did not alter the uptake of[3H]-noradrenaline (30 nM) into mice isolated vasa deferentia. Rat a-CGRP (3-100 nM) did not alter the fractional release per pulse (1.0 Hz, 100 pulses) of tritium from vasa preloaded with [3H]-noradrenaline, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In accordance with these findings immunohistochemical investigations have documented the presence of CGRP in normal as well as neoplastic thyroid C-cells (Williams et al, 1986). Another gene encoding fl-CGRP has recently been described, and shown to be transcribed in MTC (Steenbergh et al, 1985).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In accordance with these findings immunohistochemical investigations have documented the presence of CGRP in normal as well as neoplastic thyroid C-cells (Williams et al, 1986). Another gene encoding fl-CGRP has recently been described, and shown to be transcribed in MTC (Steenbergh et al, 1985).…”
mentioning
confidence: 52%
“…CGRP has been localized in discrete regions of the central nervous system, and at nerve endings adjacent to blood vessels (Rosenfeld et al, 1984). Recent work shows it to be neuropeptide, with profound effects on the cardiovascular system (Brain et al, 1985, Marshall et al, 1986.…”
mentioning
confidence: 99%
“…As with the smooth muscle of the vas deferens, in the bladder a postjunctional inhibitory effect of CGRP on excitation and contraction may be assumed. 10 ' 22 Replacement of the CGRP-enriched bladder contents by saline was followed by another brief increase in bladder contraction to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP immunoreactivity has been found extensively throughout the central 1 " 3 and peripheral nervous system. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] CGRP influences a variety of autonomic effects such as vascular tone, 4 " 7 smooth muscle contraction 8 and relaxation, 9 15 and striated muscle relaxation. 16 Additionally, recent findings of CGRP-I in sensory ganglia and nerve fibers, as well as in the adrenal medulla and pituitary gland, 17,18 suggest that CGRP may have sensory and endocrine functions.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of the intramuscular noradrenergic nerves contained NPY without any of the other neuropeptides tested for, minor populations of TH-IR nerves were identified that contained GAL, CGRP, m-ENK, SOM, or VIP coexistent with NPY. Galanin has been shown previously to be present in the human genitourinary tract where it may play a role in the regulation of smooth muscle tone and motility (Bauer et al, 1986), while CGRP has been reported to have a dosedependent postjunctional inhibitory effect on both excitation and contraction in the mouse vas deferens, mediated predominantly by activation of postganglionic noradrenergic nerve fibres (Al-Kazwini et al, 1986;Ohhanishi and Jacobowitz, 1985). All the m-ENK immunoreactivity observed by Jen et al (1997) was coexistent with TH, and is thus confined to noradrenergic nerves.…”
Section: Neuropeptidesmentioning
confidence: 90%